Relative significance of mannose-sensitive hemagglutinin and toxin-coregulated pili in colonization of infant mice by Vibrio cholerae El Tor. - Attridge, S R (1996)
A previously described in-frame deletion in mshA--the gene encoding the structural subunit of the mannose-sensitive hemagglutinin pilus--has been introduced into the chromosome of three El Tor O1 strains of Vibrio cholerae. None of the deltamshA mutants showed significant attenuation or loss of colonization potential in the infant mouse cholera model. A second mutation, created by insertion of a kanamycin resistance cartridge into deltamshA, also failed to affect in vivo behavior. In contrast, strains carrying mutations in tcpA (encoding the monomer of the toxin-coregulated pilus [TCP]) were markedly attenuated and showed dramatically impaired colonization. This result was in line with those of previous studies. Protection tests performed with antibodies to TCP and to MshA showed that only the former were able to confer immunity against El Tor O1 challenge in this model. Studies with mutants constructed from two O139 strains similarly suggest that TCP but not mannose-sensitive hemagglutinin pili are critical for colonization by strains of this serogroup.